Novel Presentation of Type 1 Wolfram Syndrome as Intracranial Hemorrhage and Longitudinally Extensive Transverse Myelitis: Neuroimaging and Angiographic Findings - Ravi P Singh; SS Jayanth; KT Seetam; Vikram V Holla; HR Arvinda; M Netravathi (Annals of Indian Academy of Neurology)
Wolfram syndrome (WS), a rare genetic neurodegenerative condition, is primarily characterized by diabetes mellitus, optic atrophy, diabetes insipidus, and sensorineural hearing loss, along with diverse systemic manifestations. Late-stage cases exhibit widespread brain atrophy. While bleeding tendencies are not commonly observed in Type 2 WS (WS2), there is a distinctive bleeding tendency that is exclusive to WS2, with no documented occurrences in Type 1 WS (WS1). Extensive documentation exists regarding various neurologic manifestations of this syndrome; however, as of now, there is no reported mention of intracranial hemorrhage, a rarity within this condition.